The uncertain impact of climate change on forest ecosystems – How qualitative modelling can guide future research for quantitative model development. (February 2016) - Herr, Alexander; Dambacher, Jeffrey M.; Pinkard, Elizabeth; Glen, Morag; Mohammed, Caroline; Wardlaw, Tim
Abstract: Climate change could significantly alter forest productivity and climax states. Hence modelling productivity under climate change will need to account for many alternative ecosystem states. We apply qualitative modelling to identify the most likely ecosystem representations for a well-researched Tasmanian forest. Its main ecosystem is a tiered forest with rainforest, wet sclerophyll and myrtaceae components. Interactions between these components are uncertain, especially under additional pressures from climate change. Qualitative modelling is a structured method to analyse these uncertainties. We identify the most appropriate models and research efforts for model development. Further, we identify research needs for interactions between root pathogens and forest components, with research on some impacts of system components on fire being ruled out. The qualitative modelling approach applied here was useful in identifying research priorities for modelling complex ecosystems, even under uncertain system understanding or deficiencies in quantitative data. Highlights: Qualitative modelling provides a way of conceptualising and addressing uncertainty in ecosystems under climate change. Limited knowledge of ecosystem interaction requires alternative ecosystem models, which results in multiple research avenues. Testing model predictions against known system dynamics enables excluding less likely models and model component linkages. Identifying less likely models and linkages focuses research efforts on critical knowledge gaps.